Revision of the genus Phthiarella Brailovsky, description of 21 new species, new distributional records, and a key to the known species (Hemiptera: Heteroptera: Coreidae: Coreinae: Anisoscelini) - Brailovsky, Harry; Barrera, Ernesto (Zootaxa, 2025)
The Neotropical genus Phthiarella Brailovsky is here revised and divided into three chromatic groups focusing on the conspicuous leg coloration, particularly the coxae, trochanters and femora: “decorata” group with 11 species, 8 are new species; “femorata” group with 10 species, 8 are new species; and “dedita” group with 5 new species. Each group is characterized and the species belonging to each one listed. Diagnostic characters of the humeri and humeral angles are given. Phthia decorata var. viridiventris Blöte, 1936 is raised to species status with the new combination Phthiarella viridiventris (Blöte, 1936) comb. nov. New distributional records for P. decorata, P. femorata and P. viridiventris are added. Photos of dorsal and ventral habitus, parameres and genital capsule of some species are provided to aid in the identification of the species. Dichotomous keys to the three species groups and the twenty-six species are included.